Optimizing Pantawid for Nutrition - Cho, Yoonyoung (World Bank, Washington, DC, 2020)
The stunting rate in the Philippines is high for the country’s level of income. Almost one in three children under age five is stunted, and the rate is significantly higher among children from low income households. The undernutrition challenge is likely to exacerbate with the economic shock and food insecurity that COVID-19 has brought. The country’s flagship safety net program, Pantawid Pamilyang Pilipino Program (4Ps), has a great potential to improve nutrition outcomes of children living in poverty, by providing cash assistance conditional upon their health check-ups and growth monitoring and raising caregiver’s knowledge and awareness on nutrition through family development sessions. There was strong evidence of the effectiveness of 4Ps on nutrition outcomes during the early stage of program implementation. Over time, however, 4Ps’ impact on nutrition faded for several reasons, most notably with the decreasing number of young children (who need nutrition the most) served by the program. This policy note proposes key areas where 4Ps can further strengthen to improve the nutrition outcomes among children in poor and vulnerable households.